2023
DOI: 10.1093/jac/dkad071
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance of Neisseria gonorrhoeae in Latin American countries: a systematic review

Abstract: Background Detailed information is needed on the dynamic pattern of antimicrobial resistance (AMR) in Neisseria gonorrhoeae in Latin America and the Caribbean (LAC). Objectives To conduct a systematic review of AMR in N. gonorrhoeae in LAC. Methods Electronic searches without language restrictions were conducted in PubMed, Embase, Cochrane Library, EconLIT, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
2
1
0
Order By: Relevance
“…For the management of urethral discharge syndrome, the guidelines recommend ceftriaxone or ciprofloxacin in a single dose, plus doxycycline for 7 days or azithromycin in a single dose (for the treatment of Chlamydia trachomatis and gonorrhea). This study showed a high resistance to ciprofloxacin (30%) among the analyzed strains; a result that coincides with the information obtained from other regions of Latin America [22], so these findings should be considered in the empirical STI treatment guidelines in Panama [31].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…For the management of urethral discharge syndrome, the guidelines recommend ceftriaxone or ciprofloxacin in a single dose, plus doxycycline for 7 days or azithromycin in a single dose (for the treatment of Chlamydia trachomatis and gonorrhea). This study showed a high resistance to ciprofloxacin (30%) among the analyzed strains; a result that coincides with the information obtained from other regions of Latin America [22], so these findings should be considered in the empirical STI treatment guidelines in Panama [31].…”
Section: Discussionsupporting
confidence: 86%
“…Of the total N. gonorrhoeae strains analyzed, we found a resistance of 38%, 40%, and 30% for penicillin, tetracycline, and ciprofloxacin, respectively, which are results that generally coincide with information obtained from other regions of the world [8]. In Latin America, for example, a high resistance of N. gonorrhoeae to antibiotics such as penicillin has been described [22] which oscillates between 17.6% and 98%, to tetracycline of between 20.7% and 90%, and between 5.9% and 89% to ciprofloxacin. The results of this study show that resistance to these three types of antibiotics has been present in all the years of isolation of the strains (2013-2018).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation